Potent and broad-spectrum anti-Candida activity of 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one, a triterpenoid from Paullinia pinnata - Benjamin Kingsley Harley; Inemesit Okon Ben; Theophilus Duku Asamoah; Cedric Dzidzor K. Amengor; Nii Korley Kortei; Priscilla Eghan; Theophilus Christian Fleischer (PLoS ONE, 2026)
Vulvovaginal candidiasis is a common infection that affects women of reproductive age, with a high prevalence among pregnant women. When left untreated, it can lead to pregnancy complications including miscarriage. The study evaluated the activity of the ethyl acetate (EtOAc) extract of Paullinia pinnata and its isolated compound 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one against drug-resistant strains and clinical isolates of Candida albicans , Candida glabrata , Candida krusei , Candida parapsilosis and Candida tropicalis . Furthermore, the effects of the combinations of 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one with voriconazole, nystatin or caspofungin on the Candida strains and isolates as well as its antibiofilm activity against the drug-resistant strains are reported in this study. The EtOAc leaves extract of P. pinnata demonstrated considerable activity against the drug-resistant Candida strains and clinical isolates with minimum inhibitory concentrations (MICs) of 31.25 to 500 µg/mL when assessed for anti- Candida activity using the microbroth dilution method. The extract was column fractionated to obtain five bulk fractions, and from the most active bulk fraction, BF4 (MIC = 3.91–31.25 µg/mL), 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one was isolated. This study is the first reported biological activity of the compound. 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one exhibited strong activity against the panel of drug-resistant Candida species with MIC ranging from 0.5 to 16 µg/mL (0.85–27.10 µM). This activity was within similar range to that of ketoconazole (MIC = 1–8 µg/mL) and amphotericin B (MIC = 0.5–2 µg/mL). When combined with voriconazole, nystatin or caspofungin using the checkerboard assay, 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one recorded synergism of 33.33% to 83.33% with the antifungals, with majority of the synergistic interactions observed against C. albicans and C. glabrata strains and isolates. 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one also demonstrated anti-biofilm activity. Its IC 50 values against the formation of biofilms and preformed biofilms of the Candida species were 15.30–46.40 μg/mL (25.91–78.60 μM) and 25.40–90.84 μg/mL (43.02–153.86 μM), respectively. In conclusion, P. pinnata possesses strong anti- Candida activity and its isolated compound, 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one displayed potent anti- Candida and anti-biofilm action. These findings identify 6α-(3’-methoxy-4’-hydroxybenzoyl)-lup-20(29)-ene-3-one as a promising anti- Candida compound warranting further investigation, including cytotoxicity in mammalian cells, before its therapeutic potential can be fully assessed.